(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology transfer is a powerful growth factor in industrial value added in the processing industries. Of course, it is important to assess the efficiency of technology transfer in the processing industry by analysing its influencing factors and discussing strategies to improve technological innovation. However, it is still difficult to measure its direct impact on the improvement or creation of value added, and one of the most relevant indicators that could measure the real impact of technology transfer is efficiency. The efficiency of the modes of technology transfer will therefore be the comparative relationship between inputs and outputs in the technology transfer activities based. It is an indicator for measuring the profitability of technology investment in industrial transformation. In our study, we will try to integrate a mathematical tool that allows us to solve optimization problems using a program operating under different constraints imposed by a model. The usefulness of this model depends on the ability to implement it, by the managers of production lines who are called upon to implement R&D, innovation or technology transfer projects. Based on panel data of processing industries that use one or more modes of technology transfer in the Souss-Massa region, this article will examine trends in the efficiency of technology transfer use, mainly as a result of technological progress and the promotion of technology transfer.